HIFDZUL LISAN PADA POLA KOMUNIKASI MENANTU PEREMPUAN DAN IBU MERTUA: (Studi Fenomenologi di Desa Kebunagung, Kecamatan Kota, Kabupaten Sumenep) - Sri Lutfiyana (Living Sufism: Journal of Sufism and Psychotherapy, 2023)
hifdzul lisan is one of the manners in Islam in speaking well or maintaining one's words in communication. hifdzul lisan on the communication patterns of daughters-in-law and mothers-in-law can form a good relationship of mutual love, appreciation and respect. However, in reality, nowadays, daughters-in-law and mothers-in-law often become conflicted in the family because there are often arguments. This research aims to reveal two things: 1) What are the forms and 2) what are the supporting and inhibiting factors of oral hifdẓul in the communication patterns of daughters-in-law and mothers-in-law in Kebunagung Village, Kota District, Sumenep Regency. The researcher is based on the phenomenological method with Al-Ghazali's theory regarding the meaning of hifdzul lisan. This research was designed using qualitative methods with a phenomenological study approach with data collection obtained by observation, interviews and documentation as well as the validity of the data. Data analysis in this research uses descriptive analysis through data presentation, data presentation and conclusions. From the research results, it can be concluded that: (1) The form of oral hifdẓul is speaking as needed, having limits, not talking too much and preferring to remain silent when speaking is harmful. Using soft local Madurese language as a symbol of respect in manners. (2) Supporting factors include support from people closest to you such as husband, distance, and reciprocal behavior. Meanwhile, the inhibiting factors are the lack of support from the husband, not controlling emotions and thoughts well, the existence of several family conflicts, the age factor for the mother-in-law in her middle age.